PWE-089 Long Term Outcomes From Leucocytapheresis In Ulcerative Colitis: A Retrospective Case Series. (9th June 2014) - Harrow, P; Kwok, H; Parkes, G; Premchand, P
Abstract : Introduction: Leucocytapheresis, the extracorporeal removal of leucocytes from patient's blood, has conflicting evidence of benefit in ulcerative colitis (UC). Numerous studies have recorded short term clinical remission rates while few have examined the long term end-points of colectomy, death and steroid free remission. Queen's Hospital, Romford is one of the largest centres performing leucoytapheresis in the UK. Here we present a retrospective case series of patients treated with the Adacolumn® leucocytapheresis filter column for UC between 2008 and 2012, designed to assess these long term end-points with follow-up to June 2013. Methods: Case notes of all patients who underwent leucocytapheresis for refractory UC were reviewed retrospectively to assess the primary end-points of colectomy and death, and the secondary end-points of clinical remission and steroid-free remission. Results: 34 patients met the entry criteria and relevant outcome data was available in 31/34. Prior to leucocytapheresis 94% of patients were steroid dependent and 91% had previously failed treatment with a thiopurine. The mean number of leucocytapheresis columns given was 7.7 +/- 0.3. Following treatment 23% underwent colectomy a median 7 months after the start of this treatment with a mean overall follow-up of 500 days. 1 patient died during the study period (from a sub-arachnoid haemorrhage). 52% experienced an initial clinical response and 32% remained in steroid-free remission at 1 year after treatment. Conclusion: The rate of colectomy after leucocytapheresis compares favourably with other rescue therapies .1, 2 The rate of steroid-free remission with leucocytapheresis is comparable to the response rates seen in randomised controlled trials of anti-TNF therapy .3 Given that the patients in this study were steroid dependent and had been refractory or intolerant to thiopurines, these results are similar to sub-group analysis of an earlier sham-controlled trial in which those patients with severe UC were more likely to respond to leucocytapheresis than sham .4 Leucocytapheresis appears to be a safe and useful option for patients with refractory UC. References: 1 Landy J, et al . Oral tacrolimus as maintenance therapy for refractory ulcerative colitis-an analysis of outcomes in two London tertiary centres. 2013 2 Aratari A, et al . Colectomy rate in acute severe ulcerative colitis in the infliximab era. 2008 3 Rutgeerts, et al . Infliximab for induction and maintenance therapy for ulcerative colitis. 2006 4 Sands, et al . A randomized, double-blind, sham-controlled study of granulocyte/monocyte apheresis for active ulcerative colitis. 2008 Disclosure of Interest: None Declared.